Attapulgite loaded vulcanized nano zero-valent iron and preparation method and application thereof

By load modification of nano zero-valent iron, the problems of easy agglomeration and oxidation are solved, the activation ability of persulfate is improved, the degradation efficiency of microplastics is significantly improved, and more efficient pollutant treatment is achieved .

CN119114104AInactive Publication Date: 2024-12-13LANZHOU JIAOTONG UNIV

Patent Information

Application Number
CN202411276374.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, nano zero-valent iron (nZVI) is prone to agglomeration and oxidation, resulting in a decrease in activity and insufficient activation ability of persulfate, affecting the degradation efficiency of microplastics.

Method used

By loading the concave and convex rod soil with a sulfide nano zero-valent iron (S-nZVI@ATP) for modification, the modified ATP and surfactant are used to improve their stability and dispersion, and the channels are cleared through acid treatment to increase the active site , enhance the catalytic effect on persulfate.

Benefits of technology

Improve the stability and dispersion of nano zero-valent iron, improve the oxidation capacity of persulfate system, enhance the degradation efficiency of microplastics, and continuously supply Fe2+ for a long time, improving the generation efficiency and generation of free radicals. Duration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005040307300000011
    Figure HDA0005040307300000011
  • Figure HDA0005040307300000012
    Figure HDA0005040307300000012
  • Figure HDA0005040307300000021
    Figure HDA0005040307300000021
Patent Text Reader

Abstract

The invention relates to the technical field of catalysts, in particular to attapulgite loaded sulfurized nano zero-valent iron as well as a preparation method and application thereof. According to the specific technical scheme, the preparation method of the attapulgite-loaded vulcanized nanoscale zero-valent iron comprises the following steps: adding modified ATP into FeSO4. 7H2O, stirring and mixing in a nitrogen atmosphere, adding anhydrous glycerol, stirring, dropwise adding a mixed solution of Na2S and NaBH4, and after the reaction is completed, centrifuging, washing and drying to obtain the S-nZVI (at) ATP composite material. According to the invention, the problem that nZVI is easy to agglomerate and oxidize in the prior art is solved, and the activation capability of the nZVI on persulfate can be greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and in particular to attapulgite-loaded sulfide nanometer zero-valent iron and a preparation method and application thereof. Background Art

[0002] Microplastics (MP) as a new pollutant have also attracted more and more attention. According to statistics, about 359 million tons of plastics are produced worldwide each year, but only 6% to 26% are recycled and harmlessly treated. Due to its biodegradability, microplastic pollutants are difficult to completely remove by traditional sewage treatment processes, and their existence seriously threatens the health of humans, animals and plants.

[0003] Microplastics are difficult to degrade in the natural environment due to their hydrophobicity, stable covalent bonds, and anti-attack functional groups. At present, most studies on the aging and degradation of microplastics are conducted under artificially controlled accelerated aging conditions. The main methods include photodecomposition, pyrolysis, hydrolysis, microbial degradation, plant degradation, and electrochemical oxidation degradation. However, these methods all have some problems. For example, the efficiency of microbial and plant degradation is low; hydrolysis and pyrolysis require a lot of energy, resulting in high energy consumption; photodecomposition usually requires ultraviolet light or a light source of a specific wavelength to activate the decomposition of microplastics, which means that additional energy is required, thereby increasing costs and environmental impacts.

[0004] Advanced oxidation processes (AOPs) are able to generate sulfate free radicals (SO4 ·- ), hydroxyl radical (·OH) and other free radicals with strong oxidizing ability, thereby initiating a free radical chain reaction, which can directly oxidize organic pollutants in water into non-toxic small molecules, or even into carbon dioxide and water. Therefore, it shows unique advantages in treating these difficult-to-degrade pollutants.

[0005] Fenton's advanced oxidation method is an efficient, low-cost, environmentally friendly chemical technology suitable for the degradation of various organic matter and wastewater treatment. However, there are also some limitations, such as: strict pH value requirements: Fenton's advanced oxidation method needs to be carried out under acidic conditions, generally requiring a pH between 2-3, so it needs to be adjusted before treating wastewater; metal ion interference: some metal ions will affect the catalytic effect of iron ions, thereby reducing the degradation efficiency of Fenton's advanced oxidation method; slow reaction rate: Fenton's advanced oxidation method has a slow reaction rate, requiring a long reaction time and a large amount of catalyst to achieve the ideal degradation effect; complex product analysis: Fenton's advanced oxidation method product analysis is difficult, requiring the use of complex instruments and technical means.

[0006] Advanced oxidation technology based on persulfate (PMS) has many advantages. The technology is stable, economical and efficient, and has attracted widespread attention from researchers and industrialized society. Persulfate has strong oxidizing properties. Compared with other oxidants such as hydrogen peroxide, persulfate is more soluble, easy to store, stable, safe and easy to control, and persulfate is an environmentally friendly oxidant. The sulfate radicals produced after persulfate activation have a higher redox potential (E0 = 2.5ev~3.1ev), which is higher than hydroxyl radicals (E0 = 2.8ev), and multiple studies have shown that the pH range of sulfate radicals is wider. In recent decades, sulfate radicals have been widely used in the degradation of various organic matter in wastewater.

[0007] Nano-zero-valent iron (nZVI) is very easy to agglomerate, oxidize, and be affected by the acidity and alkali of the solution. It is easy to generate hydroxide after the reaction, which leads to reduced activity and is not conducive to the activation of persulfate. Summary of the invention

[0008] In view of the shortcomings of the prior art, the present invention provides a attapulgite-loaded sulfide nano-zero-valent iron and a preparation method and application thereof, which solves the problems of easy agglomeration and oxidation of nZVI in the prior art and can greatly improve its activation ability for persulfate.

[0009] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0010] The invention discloses a preparation method of attapulgite-loaded sulfide nano zero-valent iron. The modified ATP is added into FeSO4·7H2O, and the mixture is stirred and mixed in a nitrogen atmosphere. Anhydrous glycerol is added. After stirring, a mixed solution of Na2S and NaBH4 is added dropwise. After the reaction is completed, the mixture is centrifuged, washed and dried to obtain a S-nZVI@ATP composite material.

[0011] Preferably, the mass ratio of FeSO4·7H2O to modified ATP is 1:1 to 3:1. 2+ Na2S is added in a molar ratio of 0.5 to 1:1, and the concentration of NaBH4 is 1.0 mol / L.

[0012] Preferably, the preparation process of the modified ATP is as follows: ATP is ultrasonically treated with acid, washed to neutrality, a surfactant is added, and an oscillation reaction is carried out at 45 to 75° C. for 1 to 3 hours. After the reaction is completed, the modified ATP is washed with ethanol, centrifuged, and dried.

[0013] Preferably, the acid is one of hydrochloric acid, sulfuric acid and nitric acid, the concentration is 1-5 mol / L, and the liquid-solid ratio of acid to ATP is 4-9:1; the mass ratio of the surfactant to ATP is 1:10-20, and the surfactant is one of alkyl trimethyl ammonium salt, ammonium chloride, ammonium nitrate and ammonium bicarbonate.

[0014] Correspondingly, the attapulgite prepared by the above preparation method is loaded with sulfide nano zero-valent iron.

[0015] Correspondingly, the attapulgite-loaded sulfide nano zero-valent iron prepared by the above preparation method is used as a catalyst in activating persulfate to degrade low-density polyethylene microplastics.

[0016] Preferably, the mass ratio of the attapulgite-loaded sulfide nano zero-valent iron to the low-density polyethylene microplastics is 0.2-0.5:1.

[0017] Preferably, during the process of degrading low-density polyethylene microplastics by attapulgite loaded with sulfide nano zero-valent iron, the pH is controlled at 3-7 and the temperature is controlled at 20-40°C.

[0018] Correspondingly, a method for degrading low-density polyethylene microplastics by catalyzing persulfate with attapulgite-loaded sulfide nano-zero-valent iron is provided, in which the microplastics are added into water, mixed evenly, and then HKSO5 is added for aging and degradation.

[0019] Preferably, the concentration of HKSO5 is 5-25 mmol / L, the aging degradation time is 1-24 h, the pH is 3-7, and the temperature is 20-40°C.

[0020] The present invention has the following beneficial effects:

[0021] 1. The present invention uses attapulgite loaded with sulfidized nano zero-valent iron to activate persulfate advanced oxidation technology to age and degrade low-density polyethylene microplastics. Compared with traditional iron fillers, nZVI can provide more active surfaces to react with pollutants more efficiently. Whether under aerobic or anaerobic conditions, nZVI can be oxidized to Fe 2+ , and then activate persulfate to produce sulfate radicals; nZVI can also react directly with persulfate to produce SO4 ·- and ·OH; in addition, Fe 2+ Fe 0 with Fe 3+The reaction regeneration can make the trivalent iron ions recycle into ferrous ions, thereby promoting the generation of free radicals and the degradation of pollutants. In view of the fact that nZVI is very easy to agglomerate, oxidize, and be affected by the acidity and alkali of the solution, and is easy to generate hydroxides after the reaction, resulting in reduced activity, in order to break through the limiting factors of its use, the present invention improves its stability and dispersibility by subjecting nZVI to load modification and other treatments, optimizes its catalytic effect on the persulfate system, and improves the oxidation capacity of the system.

[0022] 2. The preparation of the novel persulfate activator S-nZVI@ATP prepared by the present invention solves the problem of easy agglomeration and oxidation of nZVI, and effectively improves the stability and dispersibility of nZVI. At the same time, the electron release and transfer efficiency of nZVI is improved by sulfurization modification of nZVI, and the corrosion of nZVI is enhanced, thereby improving Fe 2+ The production efficiency is high, and the Fe required by the S-nZVI@ATP / PMS system is continuously supplied for a relatively long period of time. 2+ , thereby increasing SO4 ·- The generation efficiency and duration of free radicals such as ·OH.

[0023] 3. The present invention can dredge the pores of ATP and increase the number of its active sites by subjecting ATP to acid treatment. At the same time, ATP is modified using a surfactant to increase the adsorption capacity of ATP, thereby better loading the sulfide nano zero-valent iron. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Image of the device for preparing S-nZVI@ATP;

[0025] Figure 2 SEM-EDS images of S-nZVI@ATP, where a is the SEM image of S-nZVI@ATP, and b is the EDS image of S-nZVI@ATP;

[0026] Figure 3 XRD pattern of S-nZVI@ATP;

[0027] Figure 4 The SEM images of microplastics before and after oxidative degradation, where a is the SEM image before oxidative degradation of microplastics, and b is the SEM image after oxidative degradation of microplastics;

[0028] Figure 5 FT-IR images of microplastics before and after oxidative degradation;

[0029] Figure 6 XPS images of microplastics before and after oxidative degradation;

[0030] Figure 7The effects of different sulfur-iron ratios on the oxidative degradation of microplastics;

[0031] Figure 8 The effect of catalyst dosage on the oxidative degradation of microplastics;

[0032] Fig. 9 The effect of initial pH on the oxidative degradation of microplastics;

[0033] Fig.10 The effect of temperature on the oxidative degradation of microplastics;

[0034] Fig.11 The effect of PMS concentration on the oxidative degradation of microplastics;

[0035] Fig.12 The aging and degradation trend of microplastics changes over time. DETAILED DESCRIPTION

[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art.

[0038] 1. The present invention discloses a method for preparing attapulgite-loaded sulfide nano zero-valent iron, wherein modified ATP (attapulgite) is added to FeSO4·7H2O, stirred and mixed under a nitrogen atmosphere, and anhydrous glycerol is added. After stirring, a mixed solution of Na2S and NaBH4 is added dropwise. After the reaction is completed, the S-nZVI@ATP composite material is obtained by centrifugation, washing, and drying. The mass ratio of FeSO4·7H2O to modified ATP is 1:1 to 3:1. According to the S / Fe 2+ Na2S is added in a molar ratio of 0.5 to 1:1. The concentration of NaBH4 is 1.0 mol / L.

[0039] The preparation process of the modified ATP is as follows: ATP is ultrasonically treated with acid, washed to neutrality, a surfactant is added, and an oscillation reaction is carried out at 45 to 75°C for 1 to 3 hours. After the reaction is completed, the modified ATP is washed with ethanol, centrifuged, and dried. The acid is one of hydrochloric acid, sulfuric acid, and nitric acid, with a concentration of 1 to 5 mol / L, and the liquid-solid ratio of the acid to ATP is 4 to 9:1; the mass ratio of the surfactant to ATP is 1:10 to 20. The surfactant is one of alkyl trimethyl quaternary ammonium salt, ammonium chloride, ammonium nitrate, and ammonium bicarbonate.

[0040] 2. The present invention discloses the use of attapulgite-loaded sulfide nano zero-valent iron prepared by the above preparation method as a catalyst in activating persulfate to degrade low-density polyethylene microplastics.

[0041] Specifically, the mass ratio of the attapulgite-loaded sulfide nano zero-valent iron to the low-density polyethylene microplastics is 0.2 to 0.5: 1. The pH of the system for degrading low-density polyethylene microplastics by the attapulgite-loaded sulfide nano zero-valent iron is 3 to 7, and the temperature is 20 to 40°C.

[0042] The present invention will be further described below in conjunction with specific embodiments.

[0043] Example 1

[0044] Preparation of modified ATP:

[0045] ATP was ultrasonically treated with 1 mol / L hydrochloric acid for 1 hour, and then washed with deionized water to neutralize; alkyl trimethyl ammonium salt was added, and the reaction was oscillated at 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, and 75°C for 1 hour. After the reaction was completed, the product was washed with ethanol, centrifuged, and dried. The liquid-solid ratio of hydrochloric acid to ATP was 5:1; the mass ratio of the alkyl trimethyl ammonium salt to ATP was 1:15.

[0046] The results of the influence of different temperatures on the activation index of ATP showed that as the temperature increased, the activation index decreased first and then increased. At 70°C, the activation index was the highest.

[0047] The effect of different time on the activation index of ATP. According to the above preparation method, a reaction temperature of 70°C was selected, and the reaction was carried out at 1h, 2h, and 3h respectively. The results showed that the activation index no longer changed after exceeding 2.5h, and there was little point in continuing the reaction. Therefore, the optimal reaction time was determined to be 2.5h.

[0048] The effect of different surfactant dosages on the ATP activation index, at 70°C, the reaction time was 2.5h, and according to the above preparation method, the mass ratios of alkyl trimethyl ammonium salt and ATP were selected to be 1:10, 1:15, 1:20, and 1:25 for reaction. The results showed that with the increase of the mass ratio, the activation index showed a trend of first increasing and then decreasing, and the activation index was the highest when the mass ratio was 1:15.

[0049] Example 2

[0050] The present invention adopts a one-pot method to prepare the S-nZVI@ATP material.

[0051] 1. In the experiment, FeSO4·7H2O was first added to a three-necked flask filled with distilled water, and modified ATP (modified ATP prepared with the optimal parameters in Example 1) was added at a 1:1 iron-to-soil mass ratio, and then stirred under N2 protection to ensure that the solution was fully mixed. Then, an appropriate amount of anhydrous glycerol was added and stirring continued for a period of time.

[0052] 2. Then follow S / Fe 2+ Dissolve a certain amount of Na2S and an appropriate amount (concentration is 1 mol / L) of NaBH4 in pure water in a molar ratio of 1:1, stir evenly and add dropwise to the mixed solution in the three-necked flask while continuing to stir.

[0053] The above reaction processes are all carried out under N2 atmosphere, and then the mixed solution is centrifuged and washed three times with pure water and propylene glycol respectively to obtain the prepared material (Formula 3.1) (Formula 3.2) (Formula 3.3). Next, the material is placed in a vacuum drying oven for drying and filtered through a 200-mesh sieve to finally obtain the S-nZVI@ATP composite material. To ensure its stability, the composite material is vacuum-sealed and stored for use. The preparation device is as follows Figure 1 The SEM image and EDS image of the prepared S-nZVI@ATP are shown in Figure 2 As shown, the XRD pattern is Figure 3 The results show that many spherical particles of nZVI are dispersed and attached to the surface of modified ATP and the S element is introduced. Modified ATP loading and sulfurization modification solve the problem of easy agglomeration and oxidation of nZVI, thereby extending the life of nZVI particles and enhancing their reactivity.

[0054] 4Fe 3+ +3BH4 - +9H2O→4Fe 0 +3H2BO3 - +12H + +6H2↑ 3.1

[0055] Fe 2+ +2BH4 - +6H2O→Fe 0 +2B(OH)3+7H2↑ 3.2

[0056] Fe 2+ +S 2- →FeS↓ 3.3

[0057] Example 2 Degradation Experiment Design

[0058] 1. The influence of different sulfur-iron ratios

[0059] Add 100ml of ultrapure water with a pH of 7 to 5 250ml beakers, place the beakers on a digital temperature-controlled magnetic stirrer, adjust the speed and temperature (speed 400r / min, temperature 25°C), slowly add 1g of microplastic particles along the center of the vortex, and add 20mmol / L of HKSO5 when the solution is evenly mixed, and then add 0.2g of S-nZVI@ATP catalyst with sulfur-iron ratios of 0:0, 0.5:1, 0.75:1, and 1:1 in turn to activate persulfate to age and degrade microplastics. Perform 3 groups of experiments in parallel. After aging and degradation for 24 hours, place the beaker in an electric constant temperature blast drying oven and dry it at 80°C for 24 hours. After drying, filter the sample through a 200-mesh sieve, and then use a laser particle size analyzer to determine the particle size of the microplastics after aging and degradation, and determine the catalyst material with the best sulfur-iron ratio to activate persulfate aging and degradation of microplastics. The results are shown in Figure 7 As shown, the optimal sulfur-iron ratio is 0.75:1.

[0060] Then, scanning electron microscopy (SEM), Fourier transform infrared analysis (FT-IR), X-ray photoelectron spectroscopy (XPS) and other characterization analyses were performed. The SEM images, FT-IR images, and XPS images of microplastics before and after degradation were as follows: Figure 4-Figure 6 As shown. The SEM image shows that the microplastics present a spherical structure and a smooth surface before aging and degradation. After aging and degradation, the original spherical shape changes into a rough, cracked, irregular body with a layer of flocculent material on the surface, which clearly shows that the microplastic particles are partially oxidized and decomposed. FT-IR spectrum analysis shows that the absorption peaks of CO and C=O bonds are significantly enhanced, and the CH2- bond is significantly weakened. This is because the oxidation of microplastics ages and degrades, causing the long chains of microplastics to break into short chains and the surface aging to form substances with carbonyl and carboxyl functional groups. The XPS graph shows that the relative content of C decreases from the original 93.67% to 65.48%, and the relative content of O increases from the original 6.33% to 27.09%. The C content decreases significantly, and the O content increases significantly.

[0061] Subsequent experiments were conducted on this basis.

[0062] 2. Effect of catalyst dosage on degradation effect

[0063] Add 100ml of ultrapure water with pH=7 to 5 250ml beakers, place the beakers on a digital temperature-controlled magnetic stirrer, adjust the speed and temperature (speed 400r / min, temperature 25℃), slowly add 1g of microplastic particles along the center of the vortex, and add 20mmol / L of HKSO5 when the solution is evenly mixed, and then add 0.25g, 0.3g, 0.35g, 0.4g, and 0.45g of catalyst-activated persulfate with the best sulfur-iron ratio to age and degrade microplastics. Perform 3 groups of experiments in parallel. After 24 hours of aging and degradation, place the beakers in an electric constant temperature blast drying oven and dry them at 80℃ for 24h. After drying, filter the samples through a 200-mesh sieve, and then use a laser particle size analyzer to measure the particle size of the microplastics after aging and degradation, and determine the optimal dosage of the catalyst material to activate the persulfate to age and degrade the microplastics. See the results. Figure 8 As shown, the optimal dosage is 0.3g.

[0064] Subsequent experiments were conducted on this basis.

[0065] 3. Effect of initial pH on degradation effect

[0066] Add 100ml of ultrapure water with pH=3, pH=4, pH=5, pH=6, and pH=7 to 5 250ml beakers in turn, place the beakers on a digital temperature-controlled magnetic stirrer, adjust the speed and temperature (speed 400r / min, temperature 25°C), slowly add 1g of microplastic particles along the center of the vortex, and add 20mmol / L of HKSO5 when the solution is evenly mixed. Then add the catalyst with the optimal sulfur-iron ratio and the optimal dosage of persulfate to age and degrade the microplastics. Perform 3 groups of experiments in parallel. After aging and degradation for 24 hours, place the beakers in an electric constant temperature blast drying oven and dry them at 80°C for 24h. After drying, filter the samples through a 200-mesh sieve, and then use a laser particle size analyzer to determine the particle size of the microplastics after aging and degradation, and determine the optimal initial pH of the solution to activate persulfate to age and degrade microplastics. The results are shown in Table 1. Fig. 9 As shown, the optimal pH is 6. Subsequent experiments were carried out on this basis.

[0067] 4. Effect of temperature on degradation effect

[0068] Add 100 ml of ultrapure water with optimal pH to 5 250 ml beakers in turn, place the beakers on a digital temperature-controlled magnetic stirrer, adjust the speed (400 r / min), set the temperature to 20°C, 25°C, 30°C, 35°C, and 40°C, and slowly add 1 g of microplastic particles along the center of the vortex. When the solution is evenly mixed, add 20 mmol / L of HKSO5, and then add the optimal sulfur-iron ratio and the optimal dosage of catalyst-activated persulfate to age and degrade the microplastics. Perform 3 groups of experiments in parallel. After 24 hours of aging and degradation, place the beaker in an electric constant temperature blast drying oven and dry it at 80°C for 24 hours. After drying, filter the sample through a 200-mesh sieve, and then use a laser particle size analyzer to determine the particle size of the microplastics after aging and degradation, and determine the optimal temperature to activate persulfate to age and degrade the microplastics. See the results. Fig.10 As shown in the figure, the optimal temperature is 35°C. Subsequent experiments were carried out on this basis.

[0069] 5. Effect of PMS (HKSO5) concentration on degradation effect

[0070] Add 100 ml of ultrapure water with optimal pH to 5 250 ml beakers in turn, place the beakers on a digital temperature-controlled magnetic stirrer, adjust the speed (400 r / min), and slowly add 1 g of microplastic particles along the center of the vortex at the optimal temperature. When the solution is evenly mixed, add 5 mmol / L, 10 mmol / L, 15 mmol / L, 20 mmol / L, and 25 mmol / L of HKSO5, respectively. Then add the optimal sulfur-iron ratio and the optimal dosage of catalyst-activated persulfate to age and degrade microplastics. Perform 3 groups of experiments in parallel. After aging and degradation for 24 hours, place the beaker in an electric constant temperature blast drying oven and dry it at 80 ° C for 24 hours. After drying, filter the sample through a 200-mesh sieve, and then use a laser particle size analyzer to measure the particle size of the microplastics after aging and degradation, and determine the optimal PMS concentration for aging and degradation of microplastics. Results are shown in Fig.11 As shown in the figure, the optimal concentration of PMS is 20mmol / L. Subsequent experiments were carried out on this basis.

[0071] 6. Trends in aging and degradation of microplastics over time

[0072] Add 100ml of ultrapure water with pH=6 to the beaker, place the beaker on a digital temperature-controlled magnetic stirrer, adjust the speed (400r / min), and slowly add 1g of microplastic particles along the center of the vortex at a temperature of 35°C. When the solution is evenly mixed, add HKSO5 with a concentration of 20mmol / L, a sulfur-iron ratio of 0.75:1, and a catalyst dosage of 0.3g of activated persulfate to age and degrade the microplastics. After 24 hours, place the beaker in an electric constant temperature blast drying oven and dry it at 80°C for 24 hours. After drying, filter the sample through a 200-mesh sieve, and then use a laser particle size analyzer to determine the particle size of the microplastics after aging and degradation. See the results. Fig.12 As shown, in S / Fe 2+ Under the conditions of 0.75:1, catalyst dosage of 0.3g, pH=6, temperature of 35°C, and persulfate concentration of 20mmol / L, after 24h of aging degradation, the average particle size of microplastics changed dramatically.

[0073] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing attapulgite-loaded sulfide nano zero-valent iron, Features: In FeSO 4 7H 2 O, add modified ATP, stir and mix under nitrogen atmosphere, add anhydrous glycerol, stir, and then add Na 2 S and NaBH 4 After the reaction is completed, the mixed solution is centrifuged, washed and dried to obtain the S-nZVI@ATP composite material.

2. The preparation method according to claim 1, Features: The FeSO 4 7H 2 The mass ratio of O to modified ATP is 1:1 to 3:1, according to the S / Fe 2+ The molar ratio is 0.5 to 1:

1. 2 S, NaBH 4 The concentration is 1.0 mol / L.

3. The preparation method according to claim 1 or 2, Features: The preparation process of the modified ATP is as follows: ATP is ultrasonically treated with acid, washed to neutrality, a surfactant is added, and an oscillation reaction is carried out at 45 to 75° C. for 1 to 3 hours. After the reaction is completed, the modified ATP is washed with ethanol, centrifuged, and dried to obtain the modified ATP.

4. The preparation method according to claim 3, Features: The acid is one of hydrochloric acid, sulfuric acid and nitric acid, the concentration is 1-5 mol / L, and the liquid-solid ratio of the acid to ATP is 4-9:1; the mass ratio of the surfactant to ATP is 1:10-20, and the surfactant is one of alkyl trimethyl quaternary ammonium salt, ammonium chloride, ammonium nitrate and ammonium bicarbonate.

5. The attapulgite-loaded sulfide nano-zero-valent iron prepared by the preparation method according to any one of claims 1 to 4.

6. Use of attapulgite-loaded sulfide nano zero-valent iron prepared by the preparation method according to any one of claims 1 to 4 as a catalyst in activating persulfate to degrade low-density polyethylene microplastics.

7. The use according to claim 6, Features: The mass ratio of the attapulgite-loaded sulfide nano zero-valent iron to the low-density polyethylene microplastics is 0.2-0.5:

1.

8. The use according to claim 6, Features: During the process of the attapulgite loaded with sulfide nano zero-valent iron to degrade low-density polyethylene microplastics, the pH is controlled at 3-7 and the temperature is controlled at 20-40°C.

9. A method for degrading low-density polyethylene microplastics by catalyzing persulfate with attapulgite-loaded sulfidized nano-zero-valent iron prepared by the preparation method according to any one of claims 1 to 4, Features: Add microplastics to water, mix well and add HKSO 5 , undergoing aging degradation.

10. The method for degrading low-density polyethylene microplastics according to claim 9, Features: HKSO 5 The concentration is 5-25mmol / L, the aging degradation time is 1-24h, the pH is 3-7, and the temperature is 20-40℃.

Citation Information

Patent Citations

  • Modified attapulgite loaded nano zero-valent iron composite material as well as preparation method and application thereof

    CN114225897A

  • Preparation method and application of hydrophilic and hydrophobic attapulgite nano-iron material

    CN115805060A

Cited By

  • Composite material, preparation method thereof and nitrogenous wastewater treatment agent

    CN120136315A